Governing principles can guide fungicide-resistance management tactics - Bosch, F.; Oliver, Richard; Berg, F.; Paveley, N. (Annual Reviews, 2014)
Fungicide-resistance management would be more effective if principles governing the selection of resistant strains could be determined and validated. Such principles could then be used to predict whether a proposed change to a fungicide application program would decrease selection for resistant strains. In this review, we assess a governing principle that appears to have good predictive power. The principle states that reducing the product of the selection coefficient (defined as the difference between the per capita rate of increase of the sensitive and resistant strains) and the exposure time of the pathogen to the fungicide reduces the selection for resistance. We show that observations as well as modeling studies agree with the predicted effect (i.e., that a specific change to a fungicide program increased or decreased selection or was broadly neutral in its effect on selection) in 84% of the cases and that only 5% of the experimental results contradict predictions. We argue that the selection coefficient and exposure time principle can guide the development of resistance management tactics.